REFLEKSI DISKRIMINASI TOKOH PEREMPUAN DALAM - Murti Heruri (Dinamika Bahasa dan Budaya, 2013)
Sherwood Anderson (1876-1941) is one of the early twentieth-centuryAmerican authors.He is among the first American authors to explore the innernature of human being. His “hunger to see beneath the surface of lives” is bestbeing expressed in Winesburg, Ohio. This study examines the problem of neuroticanxiety of women who live in Winesburg, Ohio. The women presented seem to showa less positive nature in women. A few women are portrayed as being stupid andshameless.Men treat woman as object, only to be used. Some are defeated,subordinated and loveless marriages. They escape from their problem byemploying ‘ego defence mechanisms’. Relating to the women’s subordination andthe neurotic anxiety of women in Winesburg, Ohio, then patriarchy theory andpsychoanalysis are applied to analyze the object. Hopefully the embrace ofunderstanding, love and sympathy will overcome the constraint.KEY WORDS: women’subordination, patriarchy and defence mechanisms